If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1 + -3 = 2 Reorder the terms: -1 + -3 + 5x = 2 Combine like terms: -1 + -3 = -4 -4 + 5x = 2 Solving -4 + 5x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 5x = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 5x = 2 + 4 5x = 2 + 4 Combine like terms: 2 + 4 = 6 5x = 6 Divide each side by '5'. x = 1.2 Simplifying x = 1.2
| 3b-4-3b/2 | | 9x+4=10x+3 | | Log[4](3X)=3 | | 8(4y)-9(y)+1=0 | | -25=2v-7 | | 7=-7(v+2) | | 5x+5+2x-2=-4 | | 64/8/2 | | (8d^5)/4d^-3 | | 38=3u-10 | | 2a=-(1-a) | | 10x+2=6x+42 | | 6X^3+60X^2+96X-160=0 | | -6x=24+18x | | 5w+9=54 | | 5x+1+2x-1=-4 | | 7(x+6)-9(9x-5)=15 | | 9(x+2)-2(x-8)=14 | | lnx=sqrt(8-lnx^2) | | -4n=-9 | | y=ln(x)+c | | Ax(x-1)+B(x+1)(x-1)+C(x+1)x=x^2+4 | | -4b=11 | | 8x+2=4x-24 | | 11-6= | | -34=-2(3x+5) | | 6f+5(4f+3)= | | 6(2n+8)=102 | | 107=107(47-y) | | 4(3n-3)=48 | | 2x^2+25x+20=-x^2-8 | | 2(y-1)=3(y-6) |